2022
DOI: 10.3390/life12081127
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Detection of Clinically Useful Biomarkers for the Diagnosis of Delirium in Older People in the Emergency Department—A Case–Control Study

Abstract: Background: The identification of biomarkers associated with delirium in the emergency department could contribute to the understanding, prediction and diagnosis of this disorder. The present study was carried out to identify biomarkers included in easily and quickly obtained standard blood examinations in older patients with delirium in the emergency department. Methods: A case–control study was carried out in the emergency department of Francesc de Borja Hospital (Gandía, Valencia, Spain). Older adults (≥65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Jiang et al reported a high PLR associated with a higher incidence of delirium upon admission to the intensive care unit [155], while another group did not find any significance in PLR levels between patients who manifested postoperative delirium and those who did not [156]. Soler-Sanchis et al conducted a case-control study, discovering significantly lower values of PLTs, PLR, and MPV in patients compared to controls [157].…”
Section: Platelet Parameters As a Tool For Delirium Predictionmentioning
confidence: 99%
“…Jiang et al reported a high PLR associated with a higher incidence of delirium upon admission to the intensive care unit [155], while another group did not find any significance in PLR levels between patients who manifested postoperative delirium and those who did not [156]. Soler-Sanchis et al conducted a case-control study, discovering significantly lower values of PLTs, PLR, and MPV in patients compared to controls [157].…”
Section: Platelet Parameters As a Tool For Delirium Predictionmentioning
confidence: 99%